An Insight into the Structure-Activity Relationship of Antimicrobial Peptide Brevinin - Arnab, Md. Kamrul Hasan; Hasan, Moynul; Islam, Md. Monirul (Jordan Journal of Pharmaceutical Sciences, 2023)
Numerous amphibian species, particularly those of the genus Rana, have been found to produce linear, amphiphilic, and cationic antimicrobial peptides (AMPs). Such AMPs are gaining more attention in pharmaceutical applications due to their principal method of action, which involves penetrating and rupturing the intended cell membranes with relatively low resistance. Brevinin is a large family of AMPs extensively studied during the last few decades, primarily consisting of two groups of peptides: Brevinin-1 and Brevinin-2. These peptides are cationic and establish secondary structures in the biological membrane environment. In this discussion, we explore the effects of structural parameters (net charge, hydrophobicity, amphiphilicity, helicity, peptide length, etc.) of Brevinin on their antimicrobial activity. As a general rule, an increased net charge tends to enhance antimicrobial activity. However, it is important to note that excessive net charges can also elevate hemolytic activity. The amino acid composition significantly influences hydrophobicity and helicity, which, in turn, impact the activity of the peptides. Moreover, these structural parameters are interconnected; modifying one parameter will affect others. Striking an optimal balance in these factors will provide a Brevinin analog with the highest antimicrobial activity and the lowest hemolytic activity.